Modernism's Role in the Theory of John Martin and Edwin Denby - Morris, Gay (Edinburgh: Edinburgh University Press, 2004)
RESUMEN: Martin and Denby are often portrayed in opposition to each other. Particularly during 1940s, when they were writing for major New York newspapers, they appeared to offer competing visions of what an American dance might be. Martin supported a dance of psychological essences and as such favoured modern dance, epitomized by Martha Graham. Denby supported a dance of pure movement, shorn of story-line and in some cases thematic content. He favoured ballet and Balanchine. However, without minimizing their differences, I want to show here that the two men were in closer agreement than is at first apparent. For example, martin held views of what constituted successful ballet that were remarkably close to Denby's. However, it was not so much on specific points that Martin and Denby were aligned, but on a more general theoretical level. I will argue that they were both modernists who emphasized elements that contributed to modernism's commitment to authenticity. Martin and Denby's modernism is significant because it enabled them to position American high-art dance within an international vanguard at a time when the US was emerging as a world leader with an eye to dominating art as well as other spheres of influence. It also allowed them to treat American dance as a means of combating bourgeois rationalization, a key issue of modernity.